Nonsequential double ionization of N2 in a near-single-cycle laser pulse - Kübel, M.; Kling, Nora G.; Betsch, K. J.; Camus, N.; Kaldun, A.; Kleineberg, U.; Ben-Itzhak, I.; Jones, R. R.; Paulus, G. G.; Pfeifer, T.; Ullrich, J.; Moshammer, R.; et al. (My University, 2013)
We present a comparative study of nonsequential double ionization (NSDI) of N2 and Ar exposed to near-single-cycle laser pulses. The NSDI process is investigated using carrier-envelope-phase-tagged electron-ion coincidence spectroscopy. The measured NSDI spectra of N2 and Ar exhibit a striking resemblance. In particular, the correlated two-electron momentum distribution arising from NSDI of N2 also displays a cross-shape very similar to that reported for Ar [Bergues et al., Nat. Commun. 3, 813 (2012)]. We interpret our results in terms of recollision-excitation with subcycle depletion and discuss how this mechanism accounts for the observed similarities and differences in the ionization behavior of the two species.